ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PADA BANK PERKREDITAN RAKYAT DI PROVINSI RIAU TAHUN 2014-2019 - Imam Hanafi (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the effect of policy on loan interest rates, capital adequacy ratio (CAR), return on asset (ROA), non performing loan (NPL) and loan to deposit ratio (LDR) on lending to credit distribution at the people’s credit bank in the province of riau. The population in this study were all banking companies in riau province from 2014-2019, which amounted to 34 companies. The sampling method in this study was purposive sampling in accordance with the sampling criteria, from 34 companies, 27 companies were obtained that could be used as samples in this study. The data collection method used in this study is documentation, while the data collection method used in this study is documentation, while the data collected is about loan interest rates, capital adequacy ratio (CAR), return on assets (ROA), non performing loan (NPL), loan to deposit ratio (LDR). The data analysis method used in this study is multiple linear regression analysis. The result showed that loan interest rates, return on assets (ROA), capital adequacy ratio (CAR), non performing loan (NPL), and loan to deposit ratio (LDR) had an effect on lending to rural banks in riau province in 2014-2019. Penelitian ini bertujuan untuk menganalisis pengaruh kebijakan suku bunga kredit, capital adequacy ratio (CAR), return on asset (ROA), non performing loan (NPL) dan loan to deposit ratio (LDR) terhadap penyaluran kredit pada Bank Perkreditan Rakyat (BPR) di Provinsi Riau. Populasi dalam penelitian ini adalah semua perusahaan bank perkreditan rakyat yang ada di Provinsi Riau dari tahun 2014-2019, yang berjumlah 34 perusahaan. Metode pengambilan sampel dalam penelitian ini adalah purposive sampling yang sesuai dengan kriteria pengambilan sampel dari 34 perusahaan, didapatkan 27 perusahaan yang dapat dijadikan sampel dalam penelitian ini. Metode pengumpulan data yang digunakan dalam penelitian ini yaitu dokumentasi sedangkan data yang dikumpulkan adalah tentang tingkat suku bunga kredit, capital adequacy ratio (CAR), return on asset (ROA), non performing loan (NPL), loan to deposit ratio (LDR). Metode analisis data yang digunakan dalam penelitian ini adalah dengan menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan bahwa suku bunga kredit, return on asset (ROA), capital adequacy ratio (CAR), non performing loan (NPL), loan to deposit ratio (LDR) berpengaruh terhadap penyaluran kredit pada Bank Perkreditan Rakyat di Provinsi Riau tahun 2014-2019.